Test case prioritization with textual comparison metrics - Tumeng, R. (Institute of Electrical and Electronics Engineers Inc., 2016)
Regression testing of a large test pool consistently needs a prioritization technique that caters requirements changes. Conventional prioritization techniques cover only the methods to find the ideal ordering of test cases neglecting requirement changes. In this paper, we propose string dissimilarity-based priority assignment to test cases through the combination of classical and non-classical textual comparison metrics and elaborate a prioritization algorithm considering requirement changes. The proposed technique is suitable to be used as a preliminary testing when the information of the entire program is not in possession. We performed evaluation on random permutations and three textual comparison metrics and concluded the findings of the experiment.